2012
DOI: 10.1021/nl303610m
|View full text |Cite
|
Sign up to set email alerts
|

Design Principles for Photovoltaic Devices Based on Si Nanowires with Axial or Radial p–n Junctions

Abstract: Semiconductor nanowires (NWs) are a developing platform for electronic and photonic technologies, and many demonstrated devices utilize a p-type/n-type (p-n) junction encoded along either the axial or radial directions of the wires. These miniaturized junctions enable a diverse range of functions, from sensors to solar cells, yet the physics of the devices has not been thoroughly evaluated. Here, we present finite-element modeling of axial and radial Si NW p-n junctions with total diameters of ~240 nm and dono… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
130
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 124 publications
(138 citation statements)
references
References 29 publications
(63 reference statements)
6
130
1
Order By: Relevance
“…The ability to pattern arrays of NWs over large areas, at high density, and with robust control of their periodicity would constitute a breakthrough. Furthermore, NW design [70] and synthesis efforts should minimize the size and doping heterogeneity of NWs, because variations in such parameters limit the overall power conversion efficiency of the system [71]. Finally, though the systems cost of an assembled NW photovoltaic cell is difficult to quantify at present, synthetic advances, use of cheaper catalysts, and adoption of lower-temperature processes will drive cost reductions.…”
Section: Discussionmentioning
confidence: 99%
“…The ability to pattern arrays of NWs over large areas, at high density, and with robust control of their periodicity would constitute a breakthrough. Furthermore, NW design [70] and synthesis efforts should minimize the size and doping heterogeneity of NWs, because variations in such parameters limit the overall power conversion efficiency of the system [71]. Finally, though the systems cost of an assembled NW photovoltaic cell is difficult to quantify at present, synthetic advances, use of cheaper catalysts, and adoption of lower-temperature processes will drive cost reductions.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, finite element method (FEM) simulations 96 showed that both axial and radial NW PVs are capable of achieving high V OC values of ~0.7 V. For axial NWs, simulations show that surface recombination near the exposed junction is primarily responsible for limiting V OC below 0.7 V. For radial NWs, bulk minority carrier lifetimes < 10 ns are primarily responsible for limiting V OC . Experimental and calculated results clarify the fundamental device physics limits that must be surmounted to achieve high V OC NW PVs.…”
Section: Device Electrical Transport and Performancementioning
confidence: 99%
“…Furthermore, to reduce packing defects during assembly of NW arrays, methods should maximize end-to-end registry of NWs and reject small NW fragments leading to voids. In addition, NW design 96 and synthesis efforts should minimize NW heterogeneity with regards to size and doping, because variations in these parameters can limit the power conversion efficiency of the system 97 . Finally, although the total systems cost of an assembled NW photovoltaic is difficult to quantify rigorously, synthetic advances including nanowire growth by aerotaxy 98 , use of cheaper metal catalysts and lower temperature processes 52 will likely be a primary driver of cost reductions.…”
Section: Conclusion and Prospects For Future Researchmentioning
confidence: 99%
“…Nano-scale particles present a shorter distance for collection of minority charge carriers, but require p-i-n doping distributions in order to support a space-charge region and assist in charge separation. [28][29][30][31] 10,32 Moreover, in comparison to smooth micron-sized particles, smooth nanoparticles present more surface area per particle volume which lessens cocatalyst requirements. However, micron-sized particles absorb more light, because the optical path length depends on particle size and micron-sized particles also more effectively scatter light likely increasing the number of times light passes through each particle.…”
Section: (A) Particle Concentrationmentioning
confidence: 99%